Prognostic value of pulmonary transit time by cardiac magnetic resonance in patients with heart failure with preserved ejection fraction. (13th July 2021) - Elshibly, M; Kanagala, P; Budgeon, C; Wright, R; Jerosch-Herold, M; Gulsin, GS; Squire, IB; Ng, LL; Mccann, GP; Arnold, JR
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): National Institute for Health Research Leicester Cardiovascular Biomedical Research Centre Background: Quantifying pulmonary transit time (PTT) from cardiac magnetic resonance (CMR) first pass perfusion imaging is a novel technique for the evaluation of haemodynamic congestion in heart failure. Previous studies have demonstrated that PTT is prolonged in patients with heart failure with reduced ejection fraction (HFrEF) and that it provides independent prognostic information in this patient group. However, the potential diagnostic and prognostic roles of PTT assessment in patients with heart failure with preserved ejection fraction (HFpEF) remain to be established. Aim: To compare PTT in healthy controls and in patients with HFpEF, and to determine the prognostic value of PTT in HFpEF. Methods: In a prospective, observational study, HFpEF and age-matched control subjects underwent multi-parametric CMR at 3-Tesla, comprising quantitative left ventricular volumetric assessment using a standard steady-state free precession (SSFP) pulse sequence, and first-pass perfusion imaging at rest using a T1-weighted segmented inversion recovery gradient echo sequence (following injection of 0.04mmol/kg of contrast). PTT was calculated as the time interval between the peaks of signal intensity curves in the right and left ventricular blood pools (defined on the basal slice of the rest perfusion images). The primary endpoint was the composite of death or hospitalisation with heart failure. Results: 88 HFpEF patients (age 73 ± 9 years, 51% male, EF 56.4 ± 5.6%) and 40 controls (age 73 ± 5 years, 43% male, EF 58.5 ± 4.7%) were studied. PTT was comparable in HFpEF patients (7.7 ± 3.8s) and in healthy controls (7.5 ± 1.8, p = 0.69). Normalised to cardiac cycle lengths, PTT remained comparable in HFpEF patients and healthy controls (8.5 ± 4.0 cardiac cycles versus 7.8 ± 1.6 cardiac cycles, respectively, p = 0.19). In the HFpEF group, during median follow-up of 3.4 years, there were 38 events (25 hospitalisations with heart failure, 13 deaths); a significant relationship between survival and PTT was not demonstrated (HR 1.06 [0.99, 1.14] for a one-unit increase, p = 0.098). Conclusion: In HFpEF, PTT is not prolonged compared with PTT in healthy subjects. Unlike in HFrEF, PTT does not appear to be diagnostically or prognostically significant in HFpEF. Figure 1: Graph showing signal intensity curves in the right (red) and left (green) ventricular blood pools Figure 2: Kaplan-Meier plot showing comparable rates of the composite endpoint in patients with PTT greater/less than median PTT (8 cardiac cycles)